Advanced covalent ceramics from organosilicon polymers for sustainable energy and environment - Mujib, Shakir Bin (Kansas State University, 2022)
Controlled thermal degradation of the liquid-phase polymers of molecular precursor-derived ceramics offer them excellent engineering properties. Amorphous ceramic phase and resistance to crystallization up to 1400 °C, high-temperature stability, and intense photoluminescence are some of the remarkable functional properties of these polymer-derived ceramics (PDCs). The ever-increasing demand of high-temperature components to increase the performance efficiency in aerospace applications pushes the industry to look for a new class of materials. Simultaneously, investigations of renewable energy sources lead to the development of efficient energy storage materials. PDC route offers a promising solution to both of these applications owing to PDC’s distinct production route and functional properties. This dissertation focuses on two aspects. Firstly, the use of silicon-based PDCs to fabricate lightweight and strong ceramic matrix composites for high-temperature applications. The efficient infiltration of carbon fibers cloths (disks) and mini-bundles with boron-modified polysilazane and hafnium-modified polysilazane preceramic polymer solutions were investigated using a lab-scale, cost-effective drop coating technique. After the successful infiltration of the fibers was confirmed, the infiltrated fibers were heat-treated at different temperatures to complete the polymer-to-ceramic conversion of the preceramic polymer matrix. The boron-modified polysilazane and hafnium-modified polysilazane coated carbon fibers were crosslinked at 180 °C, followed by pyrolysis at 800 °C in inert environments to achieve Si(B)CN/CF and Si(Hf)CN/CF CMC mini-composites, respectively. Crack and defect free ceramic matric composites were achieved. The as-fabricated mini-composites were then investigated by several techniques to determine the composites’ micro-structures and properties. The effect of the boron and hafnium in the polymer-derived ceramic matrices and micro-structural development of the final ceramic composites were characterized using scanning electron microscopy (SEM), Raman spectroscopy, Fourier-transform infrared spectroscopy (FTIR), and X-ray photoelectron spectroscopy (XPS). The Raman and FTIR spectroscopies showed the complete conversion of the polymer to ceramic phase. The elemental composition and distribution of chemical bonds in the final mini-composites were determined by XPS. The mechanical properties of the mini-composites were investigated by tensile tests. Room-temperature tensile tests showed that the Si(Hf)CN/CF sample could reach a tensile strength of 790 MPa and elastic modulus of 66.88 GPa among the composites. To determine the high-temperature stability the oxidation behavior at various temperatures were studied. The oxidation study of the mini-composites showed stability of the samples up to 1500 °C. Structural and compositional changes of the oxidized samples were also elaborately investigated by XPS and SEM analyses to understand the phase change after oxidation. Secondly, the application of PDCs as free-standing, high capacity electrode materials for energy storage systems. Various preceramic polymer solutions were investigated to fabricate anode materials for lithium-ion batteries. Electrospinning technique was utilized to fabricate free-standing fiber mats from three different siloxanes oligomers. To achieve electrospun fiber mats, the short-chain siloxane oligomers were needed to be mixed with and additional spinning agent such as polyvinylpyrrolidone (PVP). The electrospun fiber mats were then crosslinked at 180 °C and pyrolyzed at 800 °C in Ar environment to obtain three types of SiOC ceramic fiber mats. The electron microscopy of the PDC fiber samples showed rigid surface structures with small diameters in the range of 0.2-3 µm. Raman, FTIR, XPS, and NMR spectroscopies were utilized to outline the ceramization stages of the SiOC fibers. 29Si MAS NMR spectra of the SiOC fibers revealed that mostly SiO4 bonds were formed in the amorphous ceramic phase, which indicated the formation on free carbon phase with limited amount of Si-C bonds after pyrolysis. The higher amount of free carbon along with the SiO-C mixed bonds in the amorphous SiOC samples enabled high lithium reversibility. As a result, when utilized as LIB electrodes, the self-supporting SiOC fiber mats showed excellent specific capacity of 866 mAh g⁻¹ electrode with a high coulombic efficiency of 72%. Even as supercapacitor electrode, the SiOC fibers maintained 100% capacitance retention over 5000 cycles at a high current density of 3 A g⁻¹. These two approaches for the synthesis of CMC mini-composites and electrode components using PDC materials offer promising potential for the various PDC chemistries to be utilized for both high-temperature and energy storage applications.
Keywords: Energy; Environment; Polymer derived ceramics; Ceramic matrix composites; Lithium-ion batteries; Supercapacitor